Factors Associated with Learners' Attitute Towards Learning Through CD-ROM Courseware: A Case Study of Discovery Center, Binariang Berhad - On, Lily (2000)
The innovation in information technology, particularly computers, has enabled a new system to deliver educational, training and learning programs. The development of the programmed courseware is based upon learning theories and principles that have been applied in traditional learning environment. On the other hand, attitude has long been recognized as important prerequisite of learning. The problem here is whether the principles and theories applied in the development of Computer-Based Training coursewares facilitate favourable learning from learners' point of view. The main purpose of this research is to identify factors associated with learners' attitudes towards Computer-Based Training using CD-ROM Coursewares. Specifically, this research seeks to determine: (i) learners' attitudes towards learning through CD-ROM coursewares; (ii) the relationships between learners' characteristics and learners' attitude toward learning through CD-ROM courseware; and (iii) the relationships between courseware characteristics and learners' attitude towards learning through CD-ROM coursewares. The respondents were the employees of Binariang Berhad who had taken any CD-ROM courseware at the Discovery Centers of Binariang Berhad and went to any Discovery Center during 27th July to 22nd August 1998. The research instrument was a set of questionnaire.